Virtually screening adults for depression, anxiety, and suicide risk using machine learning and language from an open-ended interview - Wright-Berryman, Jennifer; Cohen, Joshua; Haq, Allie; Black, David P.; Pease, James L. (Frontiers in Psychiatry, 2023)
Background: Current depression, anxiety, and suicide screening techniques rely on retrospective patient reported symptoms to standardized scales. A qualitative approach to screening combined with the innovation of Nnatural language processing (NLP) and machine learning (ML) methods have shown promise to enhance person-centeredness while detectingidentify depression, anxiety, and suicide risk from in-the-moment patient language derived from an open-ended brief interview. Objective: To evaluate the performance of NLP/ML models to identify depression, anxiety, and suicide risk from a single 5–10-minute semi-structured interview with a large, national sample. Method: 2416 interviews were conducted with 1433 participants over a teleconference platform, with 861 (35.6%), 863 (35.7%), and 838 (34.7%) sessions screening positive for depression, anxiety, and suicide risk, respectively. Participants completed an interview over a teleconference platform to collect language about the participants’ feelings and emotional state. Logistic regression (LR), support vector machine (SVM), and extreme gradient boosting (XGB) models were trained for each condition using term frequency-inverse document frequency features from the participants’ language. Models were primarily evaluated with the area under the receiver operating characteristic curve (AUC). Results: The best discriminative ability was found when identifying depression with an SVM model (AUC = 0.77; 95% CI = 0.75-0.79), followed by anxiety with an LR model (AUC = 0.74; 95% CI = 0.72-0.76), and an SVM for suicide risk (AUC = 0.70; 95% CI = 0.68-0.72). Model performance was generally best with more severe depression, anxiety, or suicide risk. Performance improved when individuals with lifetime but no suicide risk in the past three months were considered controls. Conclusion: It is feasible to use a virtual platform to simultaneously screen for depression, anxiety, and suicide risk using a five-to-ten-minute interview. The NLP/ML models performed with good discrimination in the identification of depression, anxiety, and suicide risk. Although the utility of suicide risk classification in clinical settings is still undetermined and Although suicide risk classification had the lowest performance, the result taken together with the qualitative responses from the interview can better inform clinical decision-making by providing additional drivers associated with suicide risk.